2012
DOI: 10.1590/s1516-35982012000700017
|View full text |Cite
|
Sign up to set email alerts
|

Yeast extract with blood plasma in diets for piglets from 21 to 35 days of age

Abstract: -The objective of this study was to evaluate the inclusion of yeast extract as a partial replacemer of blood plasma in piglet diets and its effect on the performance and intestinal morphometry of pigs weaned at 21 days of age. One hundred and twenty animals were randomized into blocks, with five diets (4.0% blood plasma; 2.0% blood plasma with 0.0; 1.0; 2.0 or 3.0% yeast extract), six replicates and four pigs per experimental unit. At 35 days of age, one pig per experimental unit was slaughtered in order to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
2
10
0
1
Order By: Relevance
“…On the other hand, several studies doubt that (Carlson and Veum 2000;Rigueira et al 2013). The lack of consistent results among different papers may be related to factors such as environmental stress, immune challenge levels, and the complexity of the diets used in these studies (Pereira et al 2012). The higher weight gain of animals supplemented with blood plasma may be affected by factors such as the age at weaning.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, several studies doubt that (Carlson and Veum 2000;Rigueira et al 2013). The lack of consistent results among different papers may be related to factors such as environmental stress, immune challenge levels, and the complexity of the diets used in these studies (Pereira et al 2012). The higher weight gain of animals supplemented with blood plasma may be affected by factors such as the age at weaning.…”
Section: Discussionmentioning
confidence: 96%
“…There is possibility that some elements with poor flavour or tastes may restrict the feed intake of weaning piglets. Supportively, Pereira et al (2012) indicated that the inclusion of YP can only partial replace blood plasma in piglet diets without compromising body weight gain and FCR. Moreover, Reisinger et al (2012) showed that the lower (0.1%) concentration of the yeast derivatives had a positive influence on the performance parameters of the broiler compared to those fed 0.2% yeast derivatives.…”
Section: Page 165]mentioning
confidence: 95%
“…Yeastderived protein (YP), as a yeast content separated from yeast cells, has been proposed to be a superior protein ingredient to substitute SDPP for weaning piglets (Chae et al, 2001). Yeast-derived protein generally contains amino acids and nucleotides, which have been demonstrated to possess immunoregulatory and antimicrobial capabilities (De los Santos et al, 2007;Pereira et al, 2012). Previous studies demonstrated that YP had similar effects as SDPP in increasing feed intake and body weight (BW) gain of weaning piglets (Carlson et al, 2005;Moehn et al, 2010), which nutritionally was associated with their similar digestibility of nutrients (Mateo and Stein, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Yeast-derived protein (YP), enriched with free amino acids, short chain peptides, nucleotides, and inositol (Pereira et al 2012) has been proposed to be a superior protein ingredient as an alternative to SDPP for weaning pigs. As a mixture of yeast cell contents by removing the cell wall from yeast cells (Chae et al 2001), YP possesses similar apparent (AID) and standardized (SID) ileal digestibility of amino acids with SDPP for weanling piglets (Mateo and Stein 2007;Moehn et al 2010).…”
Section: Introductionmentioning
confidence: 99%